The rise of the national-popular and its limits: communism and the cultural in Kerala - Nissim Mannathukkaren (Inter-Asia Cultural Studies, 2013)
The emergence of the communist movement in Kerala, India in a society that was charac- terized by immense divisions of caste and class is significant for understanding social transformation. What is of particular importance is the ways in which the communist activists who spoke the language of a supposedly alien ideology engaged with a populace that was predominantly agrarian and poor. This paper will look at the communist engagement with certain aspects of culture, specifically songs, folk arts and theater, in the initial years of the movement, and will argue that something akin to a national-popular will was constructed, which broke down many existing hierarchies and created new unities. But this engagement was equally characterized by many contradictions and spec- tacular failures, which dented the emerging national-popular will. The cultural, and the communist engagement with it will played a crucial role in laying the seeds of a substantive postcolonial democ- racy but only in relative terms and without necessarily conferring on the most exploited classes equal rights.